'Ba-SKY-aP with her each day at dinner': technology as supporter in the learning and management of home languages. Issue 8 (14th September 2021) - Said, Fatma F. S.
ABSTRACT: The paper describes the transformational role technology plays in the management and transmission of heritage (minority) languages (HL) in two UK-based multilingual families. Data were collected in the form of a language background survey, parental interviews, and recordings of interactional events within the home. Findings suggest that parents use technology as a language management tool within the home domain to transmit their HL through enhancing HL language practices and creating rich HL linguistic environments, which both support and seem to contradict parents' declared language beliefs. Technology allows Family members from across the world to frequently partake in everyday multilingual talk thereby strengthening HL learning and use. Interestingly, the support parents feel technology offers them in transmitting the HL reduces their own anxiety over their children's HL development whilst also unexpectedly relaxing their attitudes towards fears of (over)consumption of technology. Equally, technology appears to support children to consciously develop overt bilingual identities that they previously did not (openly) profess. The data supports the notion of technology as semiotic practice emphasising that with strategic parental support and agency from children, technology can transform the home into a hub where the learning and maintenance of the HL is advocated in multiple unprecedented ways.